The Scenic Perfomance as Subversive Negativity : radical alterity and trava sudaca perfomance in the voice of Susy Shock - Martínez, Ariel; Mora, Ana Sabrina (2020)
En ocasión de las performances escénicas de la artista Susy Shock y, en particular, de la presentación que mantiene en el plano de la intersección y la conjugación una serie de elementos que conforman una escena performática donde la monstruosidad pueda irrumpir, ofrecemos algunas reflexiones epistemológicas acerca de los límites de la representación identitaria frente a la presentación escénica. Sus performances poéticas incluyen canciones propias de géneros musicales del folklore nacional argentino (vidalas, coplas, tangos), mediante la apropiación de un producto cultural tradicional en voz de una trava. Esto produce la visibilización de una alteridad radical en la presentación simultánea de elementos que sólo es posible recobrar a partir de la interseccionalidad que se libra en el campo de la presentación, donde todos los elementos irrumpen en superposición al mismo tiempo y en un mismo lugar.
Considering the scenic performances of the artist Susy Shock, and in particular the stage presentation she makes of a so called monstrosity that maintains a series of elements that make up a scenic performance where the monstrosity can break into the field of intersection and conjugation, we offer some epistemological thoughts about the limits of identity representations versus stage presentations. Her poetic performances include songs of musical genres of Argentine folklore (vidalas, coplas, tangos), through the appropriation of a traditional cultural product in the voice of a transgender person. This produces the visibility of a radical alterity in the simultaneous presentation of elements that can only be recovered from the intersectionality that is released in the ground of presentation, where all the elements break into overlap at the same time and in the same place.
A l'occasion des performances scéniques de l'artiste Susy Shock et, en particulier, de la présentation qui entretient une série d'éléments qui composent une scène de performance où la monstruosité peut s'introduire, au niveau de l'intersection et de la conjugaison, nous proposons quelques réflexions épistémologiques sur des limites de la représentation identitaire versus la présentation scénique. Ses performances poétiques comprennent des chansons typiques des genres musicaux du folklore national argentin (vidalas, coplas, tangos), à travers l'appropriation d'un produit culturel traditionnel à la voix d'une trava. Cela produit la visibilité d'une altérité radicale dans la présentation simultanée d'éléments qui ne peuvent être récupérés que de l'intersectionnalité qui a lieu dans le domaine de la présentation, où tous les éléments se chevauchent en même temps et au même endroit.
Keywords: Performance Escénica Travesti; Interseccionalidad; Conjunción; Ajenidad Radical; Transvestite Stage Performance; Intersectionality; Conjunction; Radical Alterity; Performance Scénique Travesti^lfr; Intersectionnalité; Conjonction; Aliénation radicale